2012
DOI: 10.3390/ma5122658
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Effects on the Formation Process, Structure and Physicochemical Properties of Supported Lipid Bilayers

Abstract: Supported lipid bilayers are artificial lipid bilayer membranes existing at the interface between solid substrates and aqueous solution. Surface structures and properties of the solid substrates affect the formation process, fluidity, two-dimensional structure and chemical activity of supported lipid bilayers, through the 1–2 nm thick water layer between the substrate and bilayer membrane. Even on SiO2/Si and mica surfaces, which are flat and biologically inert, and most widely used as the substrates for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
176
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(182 citation statements)
references
References 146 publications
(245 reference statements)
6
176
0
Order By: Relevance
“…2,3 The surface structure and properties of a solid substrate signicantly determine the selfassembly process, structure and functional activity of the supported lipid membranes. 6,7 On the other hand, due to the amphipathicity and biocompatibility of lipid molecules, lipid membranes have been regarded as one of the promising coating surfaces for biomaterials especially those with hydrophobic surfaces, in the cases of protein adsorption and immunologic rejection aer implantation. 6,7 On the other hand, due to the amphipathicity and biocompatibility of lipid molecules, lipid membranes have been regarded as one of the promising coating surfaces for biomaterials especially those with hydrophobic surfaces, in the cases of protein adsorption and immunologic rejection aer implantation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The surface structure and properties of a solid substrate signicantly determine the selfassembly process, structure and functional activity of the supported lipid membranes. 6,7 On the other hand, due to the amphipathicity and biocompatibility of lipid molecules, lipid membranes have been regarded as one of the promising coating surfaces for biomaterials especially those with hydrophobic surfaces, in the cases of protein adsorption and immunologic rejection aer implantation. 6,7 On the other hand, due to the amphipathicity and biocompatibility of lipid molecules, lipid membranes have been regarded as one of the promising coating surfaces for biomaterials especially those with hydrophobic surfaces, in the cases of protein adsorption and immunologic rejection aer implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The structures and properties of substrates are crucial factors for the formation and the physical properties of SLBs. 15 There has been no report, to our knowledge, about the SLB formation directly on a PVC membrane. The lipid-containing polymers on PVC supports are the fundamental structure of the taste sensors developed by K. Toko,16,17 but the lipids are plasticized with the polymer membranes thus do not form bilayer structure.…”
Section: Introductionmentioning
confidence: 99%
“…15 After we tried various experimental parameters such the annealing temperature (4°C, 25°C and 60°C), chemical modification and treatment of the substrate (hydrophobization with hexamethyldisilazane (HMDS), thermal treatment to remove adhesive surface water layer, and hydrophilization with UV-ozone ashing), other substrate material (thermally oxidized SiO 2 /Si), and the combinations of them, we finally found that the dominant factor for the bubble formation was the thickness of the PVC/THF solution dropcast on the substrate. A transparent PVC membrane was obtained when 20 µL of the PVC/THF solution was dropcast on a 20×20 mm 2 of the Si 3 N 4 /Si substrate, or the 10 µL solution on an 8×8 mm 2 substrate (Fig.…”
Section: Fluorescence Microscopy and Fluorescence Recovery After Photmentioning
confidence: 99%
See 2 more Smart Citations